Role of dynamin-related protein 1-dependent mitochondrial fission in drug-induced toxicity - Dan Li; Yueyan Li; Wei Pan; Bo Yang; Chengxiao Fu (Elsevier, 2024)
Dynamin-related protein 1 (DRP1) is an essential controller of mitochondrial fission whose activity is tightly controlled to ensure balanced mitochondrial dynamics and maintain internal cellular homeostasis. Growing evidence suggests that DRP1-dependent mitochondrial fission plays a role in drug-induced toxicity (DIT). Therefore, understanding the molecular mechanisms underlying DIT and the precise regulation of DRP1 function will inform the development of potential therapeutic treatments for DIT. This review comprehensively summarizes the diverse DITs and their potential mechanism associated with DRP1-dependent mitochondrial fission and discusses in vivo and in vitro model studies of toxicity protection targeting DRP1.